2016
DOI: 10.3390/s16040427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Voltage Measurement on the Quantitative Identification of Transverse Cracks by Electrical Measurements

Abstract: Electrical tomography can be used as a structural health monitoring technique to identify different damage mechanisms in composite laminates. Previous work has established the link between transverse cracking density and mesoscale conductivity of the ply. Through the mesoscale relationship, the conductivity obtained from electrical tomography can be used as a measure of the transverse cracking density. Interpretation of this measure will be accurate provided the assumptions made during homogenization are valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This observation highlights the effect of the z-binding yarns in creating a conduction path/network for the current to flow in the through-thickness direction. Thus, it is expected to have good current penetration within the sample as studied in [36,48], and this ensures that the measured resistance using 4-probe technique is actually representative volume resistivity.…”
Section: Measurement Of Initial Resistancementioning
confidence: 99%
“…This observation highlights the effect of the z-binding yarns in creating a conduction path/network for the current to flow in the through-thickness direction. Thus, it is expected to have good current penetration within the sample as studied in [36,48], and this ensures that the measured resistance using 4-probe technique is actually representative volume resistivity.…”
Section: Measurement Of Initial Resistancementioning
confidence: 99%
“…Regarding the mapping technic, the accuracy decreased with the increase of material's anisotropy [115]. Selvakumaran et al [119,120] have studied the impact of the CF-EP anisotropy on the response to transverse cracks. The authors found that in the cross-ply section, the change of resistance was decreased of 40% compared to quasi-isotropic materials.…”
Section: Carbon Fibre Reinforced Epoxy (Cf-ep) As Self-sensing Materialsmentioning
confidence: 99%